The Effect of Stenting on Venous Hypertension: Results Using a Treadmill Stress Test with Invasive Pressure Measurements in Patients with Iliofemoral Venous Obstruction. (August 2018) - Kurstjens, Ralph L.M.; de Wolf, Mark A.F.; Konijn, Helena W.; Toonder, Irwin M.; Nelemans, Patricia J.; van Laanen, Jorinde H.H.; de Graaf, Rick; Wittens, Cees H.A.
Abstract : Objectives: The primary aim was to investigate whether stenting of post-thrombotic iliofemoral obstruction reduces venous hypertension. The secondary aim was to establish whether improvement in haemodynamic parameters impacts on quality of life. Methods: In this prospective observational study, 12 participants with unilateral post-thrombotic obstruction of the iliac and/or common femoral veins (CFVs) underwent a treadmill stress test with invasive pressure measurements in the CFVs and dorsal foot veins of both affected and non-affected limbs. This was performed the day before and 3 months after stenting the obstructed tract. Paired sample t -tests were used to compare the treatment effect and univariable linear regression analysis to determine the association with improvement in quality of life. Results: Before treatment, CFV pressure increased 34.8 ± 23.1 mmHg during walking in affected limbs compared with 3.9 ± 5.8 mmHg in non-affected limbs. This pressure rise decreased to 22.3 ± 24.8 mmHg after 3 months follow up compared with a 4.0 ± 6.0 mmHg increase in non-affected limbs (−26.2 mmHg difference; 95% CI –41.2 to −11.3). No such effect was found in the dorsal foot veins. The VEINES-QOL increased 25.3 ± 11.3 points after stenting and was significantly associated with a decrease in CFV pressure rise during walking (regression coefficient 0.4; 95% CI 0.1–0.6). Conclusion: Stenting of post-thrombotic iliofemoral obstruction significantly reduces venous hypertension in the common femoral vein and correlates with an improvement in the quality of life. Larger studies with a broader range of degree of obstruction need be performed to assess whether pre-stenting pressure measurements can predict post stenting clinical success.